Effect of Body Mass Index on Sperm Parameters and Sex Hormone Level in Sample of Infertile Iraqi Men - Yenzeel, Jabaar H. (Iraqi Journal of Science, 2021)
The objective of the present study was to investigate the effect of body mass index (BMI) on semen parameters, level of sex hormone and sperm DNA integrity. Semen samples were collected from (85) infertile men and (40) healthy fertile men with range of age (38.191 ± 0.84) years during their attendance at High Institute of Infertility Diagnosis and ART, Al-Nahrain University from March to June 2016. Semen samples were obtained by masturbation after 72 hours of abstinence. Seminal fluid analyses included semen volume, sperm concentration, percent sperm motility, percent sperm morphology, and sperm chromatin integrity DNA fragmentation index (DFI]). Serum samples were collected from each subject for determination the level of Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), Prolactin (PRL), and Testosterone by ELISA method. The results revealed a highly significant (P≤ 0.01) increase in BMI and immotile sperm (%), and significant(P≤ 0.05) increase in semen liquefaction time, non-progressive motility (%), round cells counts and sperm DNA fragmentation in infertile men as compared to control group, while there was a highly significant (P≤ 0.01) decrease in progressive motility (%), and a significant (P< 0.05) decrease in the sperm concentration, sperm motility (%) and normal sperm morphology (%). The results showed statistically significant (P< 0.05) positive correlations between body mass index and sperm motility, progressive motility, non-progressive motility, immotile sperm, normal sperm morphology and sperm DNA fragmentation. No significant correlations were observed between body mass index and semen liquefaction time, semen PH, sperm concentration, round cells counts and age. In respect with level of serum hormones a significant (P< 0.05) decrease in level of FSH ,LH and testosterone was found ,while the level of prolactin showed a significant (P< 0.05) increase in infertile men when compared with control group. Significant (P< 0.05) negative correlation was observed between body mass index and serum level of prolactin and testosterone, while non-significant correlations were observed between body mass index and serum level of FSH and LH. In conclusion, this study has shown that body mass index has major effect on semen characteristics and sex hormones.